Pemanfaatan Aplikasi E-Marketing Pada PT Jeah Untuk Memenangkan Persaingan Usaha - Pangestu, Harijanto; Johan, Johan; Wirawan, Erick; Widjaja, Antonius Andri; Hendra, Hendra (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this research is to design a system that could give information to customers about the provided product and also as the order media. The research method used is based on the principle of The Seven Stages of Internet Marketing to create e-marketing application, also library research, field research, analysis and designing methodology by doing survey to PT JEAH and analyzing the result. So far, the transaction process of PT JEAH is done through manual that is customer came to the store to do purchase transaction. After the e-marketing application is done, it is hoped that could give better service to customers. E-marketing concept in this system will increase efficiency and affectivity especially into order process and product information to community. Based on the research, it is concluded that with this e-marketing application as the center information and purchase media, it is hoped that the company could get loyalty from the customers and gather new market in online users.